Rubisco carboxylation kinetics and inorganic carbon utilization in polar versus cold-temperate seaweeds - Íñiguez Moreno, Concepción; Galmés, Jeroni; López-Gordillo, Francisco Javier (Oxford University Press, 2019)
Despite the high productivity and ecological importance of seaweeds in polar coastal regions, little is known about their carbon utilization mechanisms, especially the kinetics of the CO2-fixing enzyme Rubisco. We analyzed Rubisco carboxylation kinetics at 4 °C and 25 °C in 12 diverse polar seaweed species (including cold-temperate populations of the same species) and the relationship with their ability to use bicarbonate, by using 13C isotope discrimination and pH drift experiments. We observed a large variation in Rubisco carboxylation kinetics among the selected species, although no correlation was found between either the Michaelis–Menten constant for CO2 (Kc) or Rubisco content per total soluble protein ([Rubisco]/[TSP]) and the ability to use bicarbonate for non-green seaweeds. This study reports intraspecific Rubisco cold adaptation by means of either higher Rubisco carboxylation turnover rate (kcatc) and carboxylase efficiency (kcatc/Kc) at 4 °C or higher [Rubisco]/[TSP] in some of the analyzed species. Our data point to a widespread ability for photosynthetic bicarbonate usage among polar seaweeds, despite the higher affinity of Rubisco for CO2 and higher dissolved CO2 concentration in cold seawater. Moreover, the reported catalytic variation within form ID Rubisco might avert the canonical trade-off previously observed between Kc and kcatc for plant Rubiscos.
Keywords: Algas; Carbon concentrating mechanisms; Carbon fixation; Kinetics; Macroalgae; Photosynthesis; Polar; Rubisco; Seaweeds